Longer daylengths associated with poleward range shifts accelerate aphid extinction by parasitoid wasps. (20th February 2022) - Kehoe, Rachel; van Veen, Frank
Abstract: Climate change is causing the poleward range‐shift of many species, with consequent modifications to daylight regimes and potential impacts on light‐cycle activity patterns and ecological interactions. Day‐active parasitoids experiencing longer summer days associated with a poleward range shift display increased attack rates on their aphid hosts and have higher lifetime fecundity. Theory consequently predicts that with increasing photoperiod, host–parasitoid interactions would become less stable with more variable population densities and increased extinction probability. To test this prediction empirically, we conducted a multigenerational aphid‐parasitoid microcosm experiment in which we followed population dynamics under 14 and 18 h daylight treatments. As predicted, we found an increased extinction rate of both aphids and parasitoids with longer daylengths. The long‐day treatments also exhibited higher temporal variation in parasitoid numbers and increased cumulative parasitoid population size, consistent with the prediction that increased aphid extinctions are due to increased parasitoid attack rates. Our results demonstrate that light regime can affect the dynamics of interacting species and potentially limit the co‐existence of hosts and parasitoids, as well as other trophically interacting taxa where activity patterns are dependent on the light regime. This highlights the importance of the rarely considered effect of changing daylight conditions associated with climate change–driven range shifts, which could limit poleward range shifts due to changing ecological interactions. Abstract : We experimentally demonstrate higher extinction rates and variation in population size in a plant‐aphid‐parasitoid system, as predicted by theory. These environmental effects on species interactions may be a limiting factor in the latitudinal range that species can occupy, irrespective of the physiological suitability of climate.